ANALISIS PENGELOLAAN BARANG MILIK DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (Studi Pada Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Lampung) - Agus Purnomo; Supriyanto Supriyanto; Haris Setiawan (e-JKPP, 2021)
Management of Regional Property at the Regional Financial and Asset Management Agency of Lampung Province which is based on the Regulation of the Minister of Home Affairs Number 19 of 2016 concerning Guidelines for Regional Property Management, in the implementation of the presentation of the report is still not optimal and causes problems both administratively and physically so that it will be related to the results whether or not local revenue (PAD) is good. The purpose of this paper is to analyze how the management of regional property so as to increase local revenue, what aspects become obstacles and what efforts can be made. The theory that becomes a reference for analyzing is in accordance with the expert opinion put forward by George R. Teryy that good management includes Planning, Organizing, Actuating, Controlling. This research method is to use qualitative research with descriptive analysis method, the data collection technique used by the author in making this report is to use the method of observation, direct interviews with BPKAD officials in Lampung Province, besides that the author also conducts documentation studies and literature studies to support fulfillment. this research. The result of this research is that the implementation of regional property management at the Regional Financial and Asset Management Agency has implemented a good management pattern starting from Planning, Organizing, Actuating, and Controlling or in short. (POAC), although the implementation is still not optimal, and what becomes an obstacle in the management of regional property to increase regional revenue (PAD) is the change in the regulations for the organizational structure, duties and functions and work procedures of the Lampung province regional apparatus in 2019. happen in 2020, changes in the leadership of regional heads, not optimal implementation of leases and sales, the occurrence of land/land disputes, based on data in 2019 there was an increase in local revenue (PAD), while in 2020 there was a significant decrease and maximum efforts have been made by the Regional Asset Management Sector such as improving performance by placing the State Civil Apparatus (ASN) in accordance with job analysis, determining policies, and dispute resolution.